Elementary and Intermediate Algebra: Concepts & Applications (6th Edition)

Published by Pearson
ISBN 10: 0-32184-874-8
ISBN 13: 978-0-32184-874-1

Chapter 4 - Polynomials - Study Summary - Practice Exercises: 23

Answer

$x^3-2x^2-x+2$

Work Step by Step

Distribute each term of the binomial to obtain: $=x(x^2-x-2)-1(x^2-x-2)$ Distribute $x$ and $1$ to obtain $=x(x^2)-x(x)-x(2)-1(x^2)-1(-x)-1(-2) \\=x^3-x^2-2x-x^2-(-x)-(-2) \\=x^3-x^2-2x-x^2+x+2$ Combine like terms to obtain: $=x^3+(-x^2-x^2)+(-2x+x)+2 \\=x^3+(-2x^2)+(-x)+2 \\=x^3-2x^2-x+2$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.